2020
DOI: 10.3390/pr8050619
|View full text |Cite
|
Sign up to set email alerts
|

High Enzymatic Recovery and Purification of Xylooligosaccharides from Empty Fruit Bunch via Nanofiltration

Abstract: Xylooligosaccharides (XOS) are attracting an ever-increasing amount of interest for use as food prebiotics. In this study, we used efficient membrane separation technology to convert lignocellulosic materials into a renewable source of XOS. This study revealed a dual function of nanofiltration membranes by first achieving a high yield of xylobiose (a main component of XOS) from alkali-pretreated empty fruit bunch (EFB) hydrolysate, and then by achieving a high degree of separation for xylose as a monosaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Thus, this investigation revealed that the synthesized catalyst could be used up to four times before a small loss in catalytic activity occurs. XOS recovery from water can be achieved by the use of nanofiltration membranes 61 or ethanol/water extraction process. 62…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this investigation revealed that the synthesized catalyst could be used up to four times before a small loss in catalytic activity occurs. XOS recovery from water can be achieved by the use of nanofiltration membranes 61 or ethanol/water extraction process. 62…”
Section: Resultsmentioning
confidence: 99%
“…In lignocellulosic biomass pretreatment process, alkaline concentration is a significant factor affecting degradation of the ester bonds between lignin-carbohydrate matrix [35]. Various study reported that the NaOH was suitable to remove lignin barrier, which increase the accessibility of enzyme to carbohydrate [37][38][39]. Carbohydrates of lignocellulosic biomass were comprised of cellulose and hemicellulose such as glucan, xyloglucan, xylan, arabinoxylan, mannan, gluco-or galactomannan [40].…”
Section: Effect Of Naoh Pretreatment On Carbohydrate Composition Of Sicyos Angulatusmentioning
confidence: 99%
“…The monomer arabinose and (A)XOS could be separated by different membrane and chromatographic methods in order to obtain pure arabinose-rich and an (A)XOS-rich solutions [57,58]. A promising method for that was investigated by Wijaya et al [59] and it included the combination of ultra-and nanofiltrations. After the filtration steps, 90.1% xylose recovery was achieved from a xylooligosaccharides-rich, empty fruit brunch hydrolysate [59].…”
Section: Gos Yieldmentioning
confidence: 99%
“…A promising method for that was investigated by Wijaya et al [59] and it included the combination of ultra-and nanofiltrations. After the filtration steps, 90.1% xylose recovery was achieved from a xylooligosaccharides-rich, empty fruit brunch hydrolysate [59]. Hence, the first acidic hydrolysate of BSG might be further processed by membrane technology to obtain pure arabinose and AXOS-rich solutions [59] for the production of crystalline arabinose and AXOS preparation, respectively.…”
Section: Gos Yieldmentioning
confidence: 99%
See 1 more Smart Citation